Pengaruh Dukungan Sosial Orang Tua terhadap Motivasi Berprestasi Siswa di SMA Negeri 8 Kota Jambi - Humairoh, Dini; Yulianti, Yulianti; Rasimin, Rasimin (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
This research was motivated by a field phenomenon related to the decline in student achievement motivation in school caused by insufficient parental social support and some students' lower achievement motivation. This study aims to reveal the level of parental social support and student achievement motivation and the influence of parental social support on achievement motivation in students of SMA Negeri 8 Jambi City. Achievement motivation is the drive that exists in individuals to continue to do everything successfully to achieve the standards of excellence set. This research is a type of quantitative research using ex post facto methods. , Validity and reliability tests were carried out to determine the instrument's accuracy using questionnaire data collection techniques. Theme time, the data analysis technique uses formula C formula, normality test, linearity test, and simple regression at-tests and t-tests with the help of the SPSS 25 program. The sampling technique uses Stratified random sampling with a sample of 124 students. The results showed that, in general, the influence of social support of parents of students was at a high level, with a percentage of 61.33%, and achievement motivation was at a moderate level, with a rate of 58.9%. The results also showed that based on the results of the hypothesis, a significant value of 0.000<0.05 and a calculated value of > ttable or 10.962> 0.1472 were known, which means that the research hypothesis was proven to be accurate, namely that there was an influence of parental social support on the achievement motivation of SMA Negeri 8 Jambi City students.